Four activities to promote student engagement with referencing skills - Williams, Gareth J.; Emerson, Anne; Larkin, Rebecca F.; Norman, Christine (British Psychological Society, 2014)
Teaching academic writing skills in a way that engages students in deep learning is difficult and there is a risk of encouraging surface learning approaches. Moreover, linking the experience of the research process to understanding the provenance of research studies is difficult for students as they tend to experience research, referencing, citing, and related areas in disparate and unconnected ways. We report our initial experiences of designing a series of four mutually supportive tutorial activities that are based on the principles of scaffolding, social interaction, and experiential learning. The aim was to help students identify suitable research material that could be used as evidence in assignments and to promote their understanding of how evidence can be used effectively, through referencing, when writing reports and essays.